Pneumonitis after Inhalation of Mercury Vapours - JD Glezos; JE Albrecht; RD Gair (Canadian Respiratory Journal)
A 43-year-old man presented to hospital with pneumonia but only after discharge from hospital did he admit to deliberate prior inhalation of mercury. His pulmonary involvement appeared to resolve almost completely with antibiotics and supportive care. Nevertheless, persisting elevated urinary excretion of mercury required two courses of chelation therapy. No serious systemic sequelae were observed.